CONTRIBUTING FACTORS IN DEVELOPMENT OF SPEAKING SKILL - Gali Alrajafi; Yulia Wahyuningsih; Carla Maretha (SIGEH ELT : Journal of Literature and Linguistics, 2022)
Speaking is the process of building and sharing meaning through the use of verbal and non-verbal symbols, in a variety of contexts. Low motivation in speaking will be formidable reality for the teacher. The students are often reluctant to speak because they are shy and are not predisposed to express themselves in front of other people, especially when they are being asked to give personal information or opinions. The type of this research is ethnography research (realist ethnography), but the research is not stop in Ethnography but it is followed with Research and Development (R&D). Both of them are included in Qualitative Research. Language teachers always develop speaking skills by using different  techniques  and  strategies,  the  data  indicated  that  the selected  teachers  were  using  the  communicative  approach, direct method, and audio-lingual method and others.  The techniques mostly used were discussion, role play, oral report, questions and answers, conversation and debate. The way teachers assess students’ performance was effective.